2015
DOI: 10.3892/ol.2015.3896
|View full text |Cite
|
Sign up to set email alerts
|

Double primary hepatic cancer (hepatocellular carcinoma and intrahepatic cholangiocarcinoma) in a single patient: A case report

Abstract: Abstract. Double primary hepatic cancer, consisting of hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC) located separately within a single liver simultaneously, is extremely rare. The present study reports a case of double hepatic nodules, in which HCC and ICC occurred simultaneously in the right hepatic lobe. The 47-year-old male patient, who was a carrier of hepatitis B virus, was admitted to our hospital for physical examination, which revealed two liver masses. The results of initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The incidence of synchronous double primary ICC and another cancer is too low to have sufficient data. Several cases of double primary hepatic cancers with hepatocellular carcinoma and ICC were reported ( 17 19 ), but only one case report described double primary cancers with ICC and lung squamous cell carcinoma ( 20 ). Considering the rarity of double primary cancers, we suspected that pulmonary lesions were more likely to be metastatic, but we could not obtain the lung tissue, which is a limitation of this case report.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of synchronous double primary ICC and another cancer is too low to have sufficient data. Several cases of double primary hepatic cancers with hepatocellular carcinoma and ICC were reported ( 17 19 ), but only one case report described double primary cancers with ICC and lung squamous cell carcinoma ( 20 ). Considering the rarity of double primary cancers, we suspected that pulmonary lesions were more likely to be metastatic, but we could not obtain the lung tissue, which is a limitation of this case report.…”
Section: Discussionmentioning
confidence: 99%
“…18 In this case, pleural empyema occured after transdiaphragmatic rupture of HA, which led to patient's respiratory failure and death 22 days following surgery. 16,17 Cases of patients with ICC present as HA have been reported in the past decades, but pitfalls in the diagnosis are still existing. ICC is highly malignant, Li et al reported four cases of ICC that presented as HA, all of them died with 1 year.…”
Section: Discussionmentioning
confidence: 99%